Development and Evaluation of Enzyme-Linked Viral Immune Capture Assay for Detection of SARS-CoV-2 - Naif Khalaf Alharbi; Naif Khalaf Alharbi; Nosaibah Samman; Nosaibah Samman; Sadeem Alhayli; Sadeem Alhayli; Majed F. Alghoribi; Majed F. Alghoribi; Abdulrahman Almasoud; Abdulrahman Almasoud; Atef Nehdi; Atef Nehdi; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
The pandemic of COVID-19 was caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in 2019 and it has prompted unprecedented research activities for vaccines, therapeutics, and diagnostics. The real-time reverse transcriptase-polymerase chain reaction (RT-PCR) is the gold standard method of diagnosis; however, immune-based assays offer cost-effective, deployable, easy-to-read solutions for diagnosis and surveillance. Here, we present the development, optimization, and testing of an enzyme-linked viral immune capture assay (ELVICA). It utilizes the spike antigen as the detected target of the virus and antibody-coated beads to capture the virus and enrich the detection. This method can be readout by luminescent and colorimetric equipment. It can also be visualized by the imaging system, offering a variety of detection approaches. ELVICA showed specificity to SARS-CoV-2-pseudotyped viruses as compared to MERS-CoV-pseudotyped viruses. As compared to RT-PCR, ELVICA showed high compatibility in detecting the virus in patient respiratory samples, especially for samples that are below a Ct value of 32 in RT-PCR. This assay is readily adaptable for detecting other pathogens and serves as a quick and affordable diagnostic tool.